Particle Size Modification of Breadfruit Starch (Artocarpus altilis) into Nanoparticle Size Through Top Down Technique using Acid Hydrolysis - Asri Alfiyah Ningsih Nasution; Cut Fatimah Zuhra; Juliati Br. Tarigan (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Breadfruit (Artocarpus altilis) is a significant starch source, comprising up to 70.25% of its composition, and holds extensive industrial applications. However, the physicochemical properties of natural starch pose several challenges to its direct use as an industrial raw material. These challenges include high viscosity, substantial swelling power, low solubility, significant retrogradation, limited digestibility, and poor thermal stability. To address these issues, modification of the starch particle size to the nanometer scale is proposed, which is anticipated to enhance both functional and physicochemical properties. This study employs a top-down approach through 2.2 N HCl acid hydrolysis at 38°C for 24 hours. This method offers simplicity, efficiency for scale-up in industrial applications, and relatively higher stability than alternative approaches. Particle size analysis using Particle Size Analysis (PSA) revealed an average particle size of 215 nm. Fourier Transform Infrared (FT-IR) spectroscopy showed characteristic bands similar to natural starch, with slight variations in peak intensity, indicating successful acid hydrolysis and structural disruption of the molecular order. Morphological analysis revealed minimal changes in the granules' surface structure, with clumping observed due to acid hydrolysis. The resultant starch nanoparticles exhibited decreased viscosity and swelling while solubility was enhanced. Therefore, nanoparticle starch holds promising applications in food and non-food industries.